EKSPLORASARI KEGAGALAN TOUR &TRAVEL DENGAN MENGGUNAKAN VALUE PROPOSITION DARI BUSINESS MODEL CANVAS (PENELITIAN PADA PT. XYZ) - jurnalpps pps; Abdul Jalal (Jurnal Manajerial Bisnis, 2019)
This study aims to determine the business performance of a tour & travel company PT. XYZ in 2015-2018. Next to reveal the causes of failure at PT. XYZ using a value proposition from Business Model Canvas. This study uses a qualitative descriptive approach with a total of five informants. The results of the study show the current conditions that occur at PT. XYZ Tour & travel only puts forward low prices which results in customers being disappointed and never want to use their services anymore. Value proposition owned by PT. XYZ cannot be felt by its customers because customer perception is different from the perception of the company. PT XYZ's failure due to its consistent performance decreases every year and there is no suitability of targets to be achieved because there are different perceptions of the value proposition created by the company and the value received by the customer. Of the 11 value propositions there are only three that are accepted by customers, namely performance, cost reduction and convenience. While the other nine values, namely newness, customization, getting the job done, brand, design, price, risk reduction, accessbility and ability are still homework for PT XYZ.Keywords: failure, value proposition, performance, cost reduction, convenience